Kampanye ASI Eksklusif oleh Dinas Kesehatan di Kecamatan Baras 2 Kabupaten Pasangkayu - Nurdiana (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2024)
The research looked at the campaign model by using descriptive qualitative research, through the Nowak campaign model approach and Warneryd.The subject of this research consists of Public Health Center Baras 2 Pasangkayu District and the object of the research is the mother who is in charge of health promotion at Public Health Center Baras 2 and breasfeeding mother. The researcher conducted an interview to the officers of Public Health Center which served as a health promotion to convince the pregnant women and breasfeeding mother about the importance of exclusive breastfeeding during 0 months to 6 months. The results of this research have several stages, namely the effect that the campaign is expected to be carried out by Public Health Center to change the mindset of the community to be able to give breast milk to the babies, provide education through dietary counseling, eating behavior and physical activity for pregnant women and mothers breastfeed.